2019
DOI: 10.1103/physrevmaterials.3.124413
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magnetic properties in compressively strained PrVO3 thin films

Abstract: Strain engineering is an important issue in oxides thin lms to explore new functionalities. Here, a series of high quality epitaxial PrVO 3 (PVO) thin lms were grown, by Pulsed Laser Deposition (PLD) technique, as a function of thickness on (La,Sr)(Al,Ta)O 3 (100) [LSAT (100)] and LaAlO 3 (100) [LAO (100)] substrates with nominal lattice mismatch of-0.8 % and-2.9 %, respectively. The X-ray diraction revealed a constant out-of-plane lattice parameter of PVO/LSAT with increase in lm thickness, while a rather con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In fact, we have recently shown that a dead layer of ∼ 5 nm in thickness, which is composed of mainly V 4+ ions, is responsible for the increase of magnetization for low thicknesses lms [10].…”
Section: Magnetismmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, we have recently shown that a dead layer of ∼ 5 nm in thickness, which is composed of mainly V 4+ ions, is responsible for the increase of magnetization for low thicknesses lms [10].…”
Section: Magnetismmentioning
confidence: 99%
“…In fact, we have recently shown that a dead layer of ∼5 nm in thickness exists at the surface of the film, which is mainly composed of V 4+ /V 5+ ions. 11 The V 4+ /V 5+ ions can decouple the Pr 3+ ions, leading Pr atoms to unleash their strong paramagnetic response and could partially explain the increase of magnetization for low thickness films. The dead layer was also invoked to explain the small magnetic component (i.e., soft magnetic component) at low fields (∼0.2 T).…”
Section: Magnetismmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, RVO 3 films have been grown by pulsed laser deposition (PLD) [24] or by MBE [25]. While the effect of strain on the VO 6 octahedra rotations [26,27] or La motions have also been investigated in LVO thin films grown by PLD [28], tunable magnetic properties has been observed in PVO thin films either as a function of the epitaxial strain [29,30] or the chemical strain through the control of oxygen vacancy concentration [31,32].…”
Section: Introductionmentioning
confidence: 99%